ANALISIS PENGARUH WORKING CAPITAL MANAGEMENT (WCM) TERHADAP PROFITABILITAS PERUSAHAAN (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Periode Triwulan I 2019 – Triwulan II 2021) - Rangga Radeya; A. Mulyo Haryanto (Diponegoro Journal of Management, 2022)
This study aims to examine effect of working capital management (WCM) and firm profitability proxied by return on asset (ROA). Working capital management is an effort to manage current asset and current liability that is used to support the company's operations. The components of working capital management are cash conversion cycle (CCC), average payment period (APP), inventory conversion period (ICP), and current ratio (CR) were analyzed collectively on profitability. This study also used firm age as control variabel. The population in this study are manufacture company listed on Indonesian Stock Exchange in period 2019 quarter I – 2021 quarter II. The purposive sample method was used to determine the number of research samples. The number of sample are 117 manufactur company. This research used multiple linear regression using SPSS 26 program which has previously passed the classical assumption test. From the result of the analysis carried out, this study show that cash conversion cycle (CCC) have not significant positive effect to return on asset (ROA), inventory conversion period (ICP) and average payment period (APP) have significant negative effect to return on asset (ROA), while current ratio (CR) have significant positive effect on return on asset (ROA).